Toward helical-shaped diradicaloids: cyclobutenyl o-quinodimethane-bridged indeno[1,2-b]fluorenes - Qiu, Shuhai; Wang, Chaoqiang; Xie, Sheng; Huang, Xiaobo; Chen, Lanlan; Zhao, Yunhui; Zeng, Zebing (Chemical communications (Cambridge, England), 2018)
Open-shell diradicaloids have been intensively investigated recently due to their attractive and unique optical, electronic and magnetic properties. However, open-shell diradicaloids with non-planar conjugated frameworks are less studied, especially helical-shaped pi systems. In this work, we synthesized tetraindeno-based singlet biradicals in a helical geometry, bridged by a curved cyclobutenyl o-quinodimethane molecule. Large diradical characters and extremely small singlet-triplet energy gaps, as well as unusual half-field transitions (forbidden Delta M-s = 2) were revealed for these 3D diradicals.